Nanostructure development in multicomponent polymer systems and Its characterization by synchrotron X-ray scattering - Denchev, Z. (2015)
Modern synchrotron beamlines equipped with 2D detection and microfocus offer interesting possibilities for polymer characterization. This work presents several synchrotron X-ray studies performed in multicomponent polymer systems, i.e., nanostructure development under controlled strain, quantification of transcrystallinity phenomena in differently compatibilized blends and determination of structural and concentration microgradients in core-shell polymer microcapsules. First, various immiscible binary polymer blends were obtained by subsequent melt-mixing, cold drawing and selective melting/recrystallization. The resulting microfibrilar composites were irradiated under strain in a SAXS beamline. After using the CDF formalism1, the scattering of the matrix was separated from that of the oriented transcrystalline layer (TCL) and of the reinforcing fibrils, analyzing these data arrays separately (Fig. 1a). The structural changes in TCL were found to be consistent with a reversible strain-induced crystallization of matrix material. Second, a rigorous analysis of the nanostructure of the TCL in polymer-polymer microfibrilar composite was made by synchrotron WAXS (Fig. 1b). A direct relation between the mechanical properties of the composite and the thickness of the TCL was observed.